Selection of Iron-based Additives for Enhanced Anaerobic Digestion of Sludge using the Multicriteria Decision-Making Approach - Ugwu Samson (Sciendo, 2021)
Enhancement of anaerobic digestion is vital for substrate solubilization and increased biogas production at a reduced cost. The use of several iron-based additives has proven effective in improving overall bio-digester performance during anaerobic digestion sludge. This study evaluates different iron-based additives for the selection of the best additive from the alternatives using a multi-attribute decision making (MADM) approach. The weights of the attributes were computed with the entropy weight technique and the ranking of the alternatives were performed using order preference by similarity to ideal solution (TOPSIS) method. Five attributes and thirteen frequently used alternatives were selected for evaluation. The result showed that additive cost and dosages were assigned the highest weight of 62.37 % and 27.46 %, respectively. Based on the performance scores of 99.15 %, 20 mg/L of Fe3O4 nanoparticles (Fe3O4 NPs-20) ranked best (number 1) among considered alternatives for enhancement of anaerobic digestion of sludge. The outcome of this evaluation agrees with previous experimental results and suggests that the choice of an effective iron-based additive should be based on its biogas enhancement potential and cost-effectiveness (low dosage requirement and low price).